PENGARUH MARKETING ONLINE DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pembelian Produk Labbaik Chicken) - Yulius Wahyu Setiadi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
This study aims to determine the effect of Online Marketing and E-Service Quality on purchasing decisions, either partially or simultaneously. The independent variables in this study are online marketing (X1), e-service quality (X2), and the dependent variable, namely purchasing decisions (Y). In this research, the writer uses the method of collecting data by means of observation, distributing questionnaires or questionnaires. And the research location is in Labbaik Chicken, Bengkulu city. The population and sample of this research are all consumers who buy fast food products at Labbaik Chicken, and the determination of the sample in this study uses purposive sampling technique, with the criteria namely (1) Respondents who have bought food or beverage products from Labbaik Chicken Bengkulu City, (2) ) Respondents who have updated information about fast food products on their social networks, (3) Respondents who come directly to fast food restaurants. Since the population in this study is unknown, the authors use the MSI method (method of successive interval) by transforming the ordinal scale data into interval scale data, with 5-10 samples for indicators in all variables used, namely 12 indicators with The minimum sample results are 60 respondents and the maximum sample is 120 respondents, in this study the number of samples used is 120 respondents who are considered to have met the requirements. The data analysis techniques in this study the authors used several data analysis techniques, namely instrument test, classical assumption test, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been done, it can be concluded that Online Marketing (), and E-Service Quality () on the dependent variable of Purchase Decision (Y) have a significant effect, this can be seen in the F test which states the value>, namely (99.579> 3.074 ) and (sig = 0.000 <0.050), thus it can be concluded that it is accepted that the online Marketing () and E-Service Quality () variables simultaneously have a significant influence on Purchasing Decisions (Y), in Labbaik Chicken, Bengkulu City.Â Keywords:Â  Online Marketing, E-Service Quality Purchasing Decisions